2001
DOI: 10.1046/j.1365-2494.2001.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of water‐soluble carbohydrate in perennial ryegrass (Lolium perenne L.): milk production from late‐lactation dairy cows

Abstract: Eight multiparous Holstein±Friesian dairy cows in late lactation were used to investigate the potential of using perennial ryegrass with a high concentration of watersoluble carbohydrate (WSC) to increase the ef®ciency of milk production. After a pretreatment period on a common pasture, the cows were each given ad libitum access to one of two varieties of zero-grazed grass continuously for 3 weeks. Treatments were: high sugar (HS), an experimental perennial ryegrass variety bred to contain high concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
374
16
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(427 citation statements)
references
References 48 publications
34
374
16
3
Order By: Relevance
“…The relatively small and non-significant dietary effect on NUE contrasted with results from cows fed a diet of around 3.2% N with elevated WSC in the diet, which showed improvement in NUE (Miller et al, 2001). In this study, the proportion of NI excreted in urine (UN/NI) was high (on average >48%; Table 3) compared with results from lactating dairy cows studies (Miller et al, 2001;Moorby et al, 2006).…”
Section: N Metabolismcontrasting
confidence: 71%
See 1 more Smart Citation
“…The relatively small and non-significant dietary effect on NUE contrasted with results from cows fed a diet of around 3.2% N with elevated WSC in the diet, which showed improvement in NUE (Miller et al, 2001). In this study, the proportion of NI excreted in urine (UN/NI) was high (on average >48%; Table 3) compared with results from lactating dairy cows studies (Miller et al, 2001;Moorby et al, 2006).…”
Section: N Metabolismcontrasting
confidence: 71%
“…Results from feeding cows on 3.2% dietary N (in the DM) showed that it was possible to decrease UN/FN by around 27% (Miller et al, 2001). Such change of N excretion was achieved either through increasing FN, as a function of increasing DMI or decreasing UN, as a function of increasing rumen microbial protein synthesis (Miller et al, 2001). Our goats were fed high dietary N (on average 4.5% of DM) and high WSC (on average 26.9% of DM), and there was no effect on UN/FN (Table 3).…”
Section: N Metabolismmentioning
confidence: 99%
“…In Wales, the potential of using perennial ryegrass with enhanced levels of water-soluble carbohydrates (WSC) was investigated in dairy cows using experimental perennial ryegrass varieties bred to contain a high concentration of WSC (Miller et al, 2001;Moorby et al, 2006). The concept is that provision of readily available energy can have a significantly positive influence on N utilisation efficiency and animal performance.…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%
“…Perennial ryegrass (Lolium perenne L.) is the most widely used species (Burgon et al 1997) and, as feed costs can make up as much as 35% of the total production cost (Nix 2009), the nutritional value of this fodder has a major impact on the eYciency and proWtability of animal production systems. It is important that ruminant feeds provide the animal with an easily fermentable source of energy to the rumen (Miller et al 2001) and carbohydrates generally provide this. However, the energy content of grass forages can sometimes be rather low for eYcient fermentation in the rumen and Miller et al (2001) showed experimentally that feeding grass cultivars containing a high water-soluble carbohydrate (WSC) content gave rise to increased milk and meat production.…”
Section: Introductionmentioning
confidence: 99%
“…It is important that ruminant feeds provide the animal with an easily fermentable source of energy to the rumen (Miller et al 2001) and carbohydrates generally provide this. However, the energy content of grass forages can sometimes be rather low for eYcient fermentation in the rumen and Miller et al (2001) showed experimentally that feeding grass cultivars containing a high water-soluble carbohydrate (WSC) content gave rise to increased milk and meat production. Furthermore, their study demonstrated that the high sugar content of these cultivars also reduced nitrogen partitioning into urine and thus can help to lower ammonia emissions to the environment.…”
Section: Introductionmentioning
confidence: 99%